Polifonia como recurso semântico-pragmático na construção de ethos em discursos políticos de Ottomar Pinto - Queiroz, Raphaela Fernandes dos Santos Borges de (2015)
This study aims to analyze how Brigadier Ottomar de Souza Pinto projected his political image into his speeches to become the governor of the State for four times, 1979, 1991, 2004 and 2006. For that, his tenure speeches emitted when he was elected for the first time were used as corpus, as well as his talks reproduced in journalistic materials published in three periodicals: Jornal de Roraima, Diário de Roraima and Folha de São Paulo. Ottomar`s audios transcribed on Minutes from Legislative Sessions and other discursive genres such as letters and telex were also collected. Polyphony notion has enabled the identification of several enunciated perspectives current in Ottonar`s speeches, enabling to track what line of argument he, as speaker, wanted make evident in his speeches and what he intended annul. On the other hand, in an integrated way, the concept of discursive ethos was adopted in order to verify how the speaker organizes those points of view to build his image during the enunciation. Thereby, with the analysis of the selected corpus, it is found that Ottomar Pinto projects different ethé to persuade the interlocutors to adopt his political project for the State of Roraima, evidencing the images of a democratic, religious, military and xenophobic/anti-indigenous politician.